Investigating The Seasonal Variations Of Event, Recent, And Pre-Recent Runoff Components in A Pre-Alpine Catchment Using Stable Isotopes and An Iterative Hydrograph Separation Approach (Global Journal of Science Frontier Research, 2023)
An analysis of the runoff generation processes in terms of event recent and pre-recent runoff components is demonstrated for the Swiss pre-Alpine Alp catchment 46 4 km2 and two smaller tributaries Erlenbach 0 7 km2 and Vogelbach 1 6 km2 whereas recent water is understood as the contribution of the respective three prior rainfall-runoff events A four-years time series of daily stable water isotope data in stream water and precipitation is used for the analysis of seasonal variations In addition high-frequency data 10 minutely intervals are used for a detailed visualization of the rapid mobilization of recent water for single events An iterative extension of the standard two-component hydrograph separation method is applied this approach can be interpreted as a discretization of the catchment water and tracer mass balance along the event and pre-event time axis Furthermore the calculated event recent and pre-recent runoff components can be used to estimate time-varying backward travel time distributions For the Alp catchment and its tributaries a nivale runoff regime can be shown in which the event water component generally displays its maximum 32 during August The highest recent water fractions 55-77 can be expected at the beginning of winter December January whereas the lowest fractions 7-14 were found at the end of autumn November In return higher pre-recent water fractions can be found in the summer July 60-82 and in the middle of autumn October 64-74 The two tributaries expose an additional peak of pre-recent water in the snowmelt season April 47-62 and at this time also the lowest event water fractions 6-8 can be expected For the Alp catchment the event component 29-32 and recent water component 56 clearly exceeded the pre-recent component 17-21 in August and September after the month of July which is characterized by relatively low precipitation high evapotranspiration and low soil moisture This may be an important finding regarding the expected dryer summers in middle Europe in the near future
Keywords: hydrology; runoff generation; stable isotopes; balance equations; hydrograph separation; travel time